2011
DOI: 10.3109/09637486.2011.620946
|View full text |Cite
|
Sign up to set email alerts
|

The inhibiting activity of areca inflorescence extracts on human low density lipoprotein oxidation induced by cupric ion

Abstract: The oxidative modification of human low density lipoprotein (LDL) plays a significant role in atherosclerosis. In this study, the inhibiting activity of areca inflorescence extracts (AIEs) on LDL oxidation was investigated by an in vitro study with Trolox as the standard antioxidant. The kinetics of LDL oxidation, thiobarbituric acid reactive substances assay, ferric-reducing antioxidant power assay and copper chelation assay were also evaluated to assess the antioxidant activities of AIEs, and the results rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In addition to the known alkaloid components, our analysis has revealed the presence of phenolic acids, amino acids and their derivatives, lignans, coumarins, lipids, and quinones, all of which contribute to the superior medicinal value of areca nut seeds produced in China. Research has shown that areca nut seeds exhibit many pharmacological activities, such as antioxidant, antibacterial, antihypoglycaemic, anti‐inflammatory, and antiparasitic activities; promote digestive functions; and are valuable traditional medicines for treating parasitic disease, dyspepsia, and gastrointestinal diseases 6,12,15 . Therefore, compared with ASSA, ASCN exhibits better properties.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to the known alkaloid components, our analysis has revealed the presence of phenolic acids, amino acids and their derivatives, lignans, coumarins, lipids, and quinones, all of which contribute to the superior medicinal value of areca nut seeds produced in China. Research has shown that areca nut seeds exhibit many pharmacological activities, such as antioxidant, antibacterial, antihypoglycaemic, anti‐inflammatory, and antiparasitic activities; promote digestive functions; and are valuable traditional medicines for treating parasitic disease, dyspepsia, and gastrointestinal diseases 6,12,15 . Therefore, compared with ASSA, ASCN exhibits better properties.…”
Section: Resultsmentioning
confidence: 99%
“…Research has shown that areca nut seeds exhibit many pharmacological activities, such as antioxidant, antibacterial, antihypoglycaemic, anti-inflammatory, and antiparasitic activities; promote digestive functions; and are valuable traditional medicines for treating parasitic disease, dyspepsia, and gastrointestinal diseases. 6,12,15 Therefore, compared with ASSA, ASCN exhibits better properties. These findings provide a solid theoretical foundation for the future clinical application of these seeds.…”
Section: Differential Metabolites Of Areca Nut Seeds From Different C...mentioning
confidence: 99%
See 2 more Smart Citations